(untitled) (Journal of Educational Sciences, 2022)
The article in the form of a review analyzes new research approaches of pedagogical design in comparison with the Kazakh features of this field on the example of textbooks on pedagogical design at Oxford University. The authors, asking the questions “what to teach in the 21st century and how to prepare students for the challenges of the digital age”, try to answer these questions by analyzing textbooks used in the educational process of the world’s leading universities. Today, Internet resources are becoming more accessible to students and the more their digital skills, we must organize the learning process in such a way that they can organize and control their personal development independently. The authors, exploring the functions of learning in the context of electronic and mobile technologies, review the techno-oriented future of education and raise the question of new possibilities of pedagogical science, enriched and changing by information and communication technologies, virtual reality, network space, the development of artificial intelligence, etc. The researchers express confidence that these textbooks will be interesting and useful for teachers, teachers, students in changing and updating their digital thinking. As well as textbooks on the digitalization of pedagogy and conducting research in the field of education – as leading manuals, they will undoubtedly be useful in the process of designing new educational content for developers and users of virtual learning resources. Key words: Digital pedagogy, Internet resources, virtual reality, network space, information and communication technologies, digital skills, pedagogical design, open Internet resources, open educational resources, educational design, student as producer.